2006
DOI: 10.1021/jp0614244
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Mechanical Investigation of the Atmospheric Reaction CH3O2 + NO

Abstract: The important stationary points on the potential energy surface of the reaction CH(3)O(2) + NO have been investigated using ab initio and density functional theory techniques. The optimizations were carried out at the B3LYP/6-311++G(d,p) and MP2/6-311++G(d,p) levels of theory while the energetics have been refined using the G2MP2, G3//B3LYP, and CCSD(T) methodologies. The calculations allow the proper characterization of the transition state barriers that determine the fate of the nascent association conformer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 33 publications
4
39
0
Order By: Relevance
“…No rate measurements have been reported above ∼400 K, whereas numerous investigations are available at low temperatures relevant to atmospheric chemistry research. Recent ab initio calculations of the potential energy surface of NO + CH 3 OO by Zhao et al [104] and Lesar et al [105] have confirmed that the reaction follows an addition/elimination mechanism through the intermediate adduct CH 3 OONO * followed either by direct cleavage of the peroxy bond or rearrangement to CH 3 ONO * 2 before breakage to NO 2 + CH 3 O. The reaction involving C 2 H 5 OO is expected to follow an analogous mechanism.…”
Section: No X /Alkylperoxyl Reactionsmentioning
confidence: 94%
“…No rate measurements have been reported above ∼400 K, whereas numerous investigations are available at low temperatures relevant to atmospheric chemistry research. Recent ab initio calculations of the potential energy surface of NO + CH 3 OO by Zhao et al [104] and Lesar et al [105] have confirmed that the reaction follows an addition/elimination mechanism through the intermediate adduct CH 3 OONO * followed either by direct cleavage of the peroxy bond or rearrangement to CH 3 ONO * 2 before breakage to NO 2 + CH 3 O. The reaction involving C 2 H 5 OO is expected to follow an analogous mechanism.…”
Section: No X /Alkylperoxyl Reactionsmentioning
confidence: 94%
“…This article describes a study on the exploration of isomers, isomerization reactions, as well as their reaction routes for H 3 CNO 3 using SHS‐ADDF. Studies on H 3 CNO 3 were reported recently in relation to combustion and atmospheric chemistry . The reaction channels for some isomers of H 3 CNO 3 including nitromethanol (HOCH 2 NO 2 ) and nitrosooxymethnol (HOCH 2 ONO) were elucidated using hybrid density‐functional‐theory (DFT) B3LYP method in connection with radical‐molecule reaction of CH 2 OH with NO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The reaction channels for some isomers of H 3 CNO 3 including nitromethanol (HOCH 2 NO 2 ) and nitrosooxymethnol (HOCH 2 ONO) were elucidated using hybrid density‐functional‐theory (DFT) B3LYP method in connection with radical‐molecule reaction of CH 2 OH with NO 2 . The reaction channels involving methyl nitrate (H 3 CONO 2 ) and methyl peroxynitrite (H 3 COONO) related to atmospheric systems were studied in different levels of calculations . We assumed that interesting chemistry would be discovered more from the GRRM for H 3 CNO 3 because of its potential of the formation of various functional groups, including OH, OO, OOH, OOO, CO, CHO, COOH, COOOH, CN, NH, NH 2 , NO, NO 2 , NO 3 , NOO, ONO, NOH, NOOH, NHOH, CH, CH 2 , and CH 3 , which can compose various chemical structures.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison to the corresponding theoretical data for CH 3 ONO 2 [32] demonstrates the significant geometrical changes caused upon substitution of the methylic hydrogens by chlorine and fluorine atoms. Comparison is also made with recent experimental and theoretical findings for CF 3 ONO 2 [33], which shows a good overall agreement between the present theoretical results and the literature data for the perfluorinated methyl nitrate.…”
Section: Structural and Frequency Resultsmentioning
confidence: 85%
“…The computational modeling of the nitrate formation channel has also been the subject of many theoretical efforts focused primarily on the simplest system CH 3 O 2 +NO. In all theoretical investigations, the mechanism of the reaction was found to involve the formation of both conformers of the nascent association methylperoxy nitrite adduct [26][27][28][29][30][31][32]. The two distinct conformeric structures have been characterized with respect to the ONOO dihedral angle as the cis-perp and the trans-perp configurations, where the perp notation refers to the nearly perpendicular geometry of the carbon atom of the attached methyl group.…”
Section: Introductionmentioning
confidence: 99%